PENGARUH BEBAN OPERASIONAL DAN PENDAPATAN OPERASIONAL TERHADAP PENGEMBALIAN ASET PT KALBE FARMA TBK - Moses Sirait; Rachmaniar Myrianda Dwiputri; Muhammad Kausar (Jurnal Ekonomi dan Industri, 2025)
This study aims to determine the effect of operating expenses and operating income on return on assets. This research study was conducted at one of the healthy sectoc companies listed on the Indonesia Stock Exchange (IDX), namely PT Kalbe Farma Tbk. Dana analysis using multiple and partially linear regression analysis. The research findings indicate that operational factors namely operating expenses and operating income have a significant simultaneous effect on return on assets at PT Kalbe Farma Tbk. Partially, operating income has a positive and significant impact on return on assets. Conversely, operating expenses have a negative and significant effect on return on assets